The Relationship Between Critical Thinking Skills and Learning Outcomes of Grade III Elementary School Students - Styoharini, Hani Fadillah; Firmansah, Deri; Hasnanto, Anton Tri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the relationship between critical thinking skills and the learning outcomes of third-grade elementary school students. The research method used in this study is a quantitative approach with a correlational research type. The population in this study consists of all third-grade elementary school students totaling 19 individuals. The data collection technique used was a test to obtain data on critical thinking skills and learning outcomes. The prerequisite tests used are the normality test and the linearity test. The data analysis technique in this study uses Pearson correlation (Product Moment Correlation). The findings of this research indicate that there is a significant relationship between critical thinking skills and the learning outcomes of third-grade elementary school students.